2010
DOI: 10.1089/fpd.2010.0582
|View full text |Cite
|
Sign up to set email alerts
|

Foodborne Proportion of Gastrointestinal Illness: Estimates from a Canadian Expert Elicitation Survey

Abstract: The study used a structured expert elicitation survey to derive estimates of the foodborne attributable proportion for nine illnesses caused by enteric pathogens in Canada. It was based on a similar study conducted in the United States and focused on Campylobacter, Escherichia coli O157:H7, Listeria monocytogenes, nontyphoidal Salmonella enterica, Shigella spp., Vibrio spp., Yersinia enterocolitica, Cryptosporidium parvum, and Norwalk-like virus. For each pathogen, experts were asked to provide their best esti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 14 publications
2
39
0
1
Order By: Relevance
“…In our earlier report on survey responses for foodborne proportion of illness (Ravel et al, 2010), only experts who selfassessed their pathogen expertise as 3 ( = medium, some direct experience but wide reading) or higher were used in the analysis. Although we recognized that some self-assessments may have been inflated, there was no correlation between expertise level (3, 4, or 5) and estimates of foodborne proportion of illness.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In our earlier report on survey responses for foodborne proportion of illness (Ravel et al, 2010), only experts who selfassessed their pathogen expertise as 3 ( = medium, some direct experience but wide reading) or higher were used in the analysis. Although we recognized that some self-assessments may have been inflated, there was no correlation between expertise level (3, 4, or 5) and estimates of foodborne proportion of illness.…”
Section: Discussionmentioning
confidence: 99%
“…The tool for the Canadian survey was adapted from the work of Hoffmann et al (2006) with permission of the authors and it is described in Ravel et al (2010). In the first part of the survey, respondents provided details on their academic training and work experience and a self-assessment of their expertise with respect to each pathogen and each food group.…”
Section: Survey Toolmentioning
confidence: 99%
See 2 more Smart Citations
“…European data demonstrated that eggs and egg products were the most important food vehicles for Salmonella (10). Food-specific attribution has been done previously in Canada twice using expert elicitation and once using outbreak data (16,17,18). All three identified poultry meat as the most likely source of Salmonella infections.…”
Section: Discussionmentioning
confidence: 99%